2014
DOI: 10.1037/cou0000036
|View full text |Cite
|
Sign up to set email alerts
|

Perfectionism, neuroticism, and daily stress reactivity and coping effectiveness 6 months and 3 years later.

Abstract: The present study addressed a fundamental gap between research and clinical work by advancing longitudinal explanatory conceptualizations of stress and coping processes that trigger daily affect in the short- and long-term for individuals with higher levels of personality vulnerability. Community adults completed measures of 2 higher order dimensions of perfectionism (personal standards [PS], self-criticism [SC]), neuroticism, and conscientiousness. Then, 6 months later and again 3 years later, participants co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

21
106
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 79 publications
(137 citation statements)
references
References 61 publications
21
106
2
Order By: Relevance
“…6 Nevertheless, it is part of several measures of perfectionism, and we decided to explore it to compare our results with those from studies which also included this dimension. Our results showed that organization was the only perfectionism dimension Finally, the finding that maladaptive perfectionists use low adaptive CER strategies that lead to NA increase complements the results of Dunkley et al, 26,27 showing that low task-oriented coping mediated the association between maladaptive perfectionism and psychological distress. Then, when maladaptive perfectionists engage in problem-focused and positive reinterpretation, they may experience greater decreases in negative emotions, such as in sadness.…”
Section: Mediation Role Of Adaptive Cer Mechanismssupporting
confidence: 63%
See 4 more Smart Citations
“…6 Nevertheless, it is part of several measures of perfectionism, and we decided to explore it to compare our results with those from studies which also included this dimension. Our results showed that organization was the only perfectionism dimension Finally, the finding that maladaptive perfectionists use low adaptive CER strategies that lead to NA increase complements the results of Dunkley et al, 26,27 showing that low task-oriented coping mediated the association between maladaptive perfectionism and psychological distress. Then, when maladaptive perfectionists engage in problem-focused and positive reinterpretation, they may experience greater decreases in negative emotions, such as in sadness.…”
Section: Mediation Role Of Adaptive Cer Mechanismssupporting
confidence: 63%
“…20,22,23 Similarly, EC were prospectively associated with high use of avoidant coping and with low use of problem-focused and positive reinterpretation. 27 In our study, maladaptive perfectionism was also related to increased perceived distress and decreased perceived coping. These results confirm the literature findings, suggesting that perfectionism is implicated in stress generation, anticipation, enhancement and maintenance.…”
Section: Mediation Role Of Adaptive Cer Mechanismsmentioning
confidence: 76%
See 3 more Smart Citations